2018
DOI: 10.3389/fgene.2018.00065
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Intellectual Disability and Autism Gene Cc2d1a and Its Homolog Cc2d1b Differentially Affect Spatial Memory, Anxiety, and Hyperactivity

Abstract: Hundreds of genes are mutated in non-syndromic intellectual disability (ID) and autism spectrum disorder (ASD), with each gene often involved in only a handful of cases. Such heterogeneity can be daunting, but rare recessive loss of function (LOF) mutations can be a good starting point to provide insight into the mechanisms of neurodevelopmental disease. Biallelic LOF mutations in the signaling scaffold CC2D1A cause a rare form of autosomal recessive ID, sometimes associated with ASD and seizures. In parallel,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Furthermore, the loss of Lgd function drives the over-proliferation of the imaginal discs, a phenotype that can be rescued by the expression of human CC2D1A or CC2D1B, indicating a functional overlap between these proteins (Drusenheimer et al., 2015). This redundancy was also observed in mammal models, as double CC2D1A/CC2D1B knockout mice died early during embryonic development (Zamarbide et al., 2018), but the deletion of CC2D1A or CC2D1B genes alone does not induce developmental defects (Drusenheimer et al., 2015, Zamarbide et al., 2018). However, non-redundant roles of these proteins are indicated by the perinatal death of CC2D1A-deficient mice (Al-Tawashi et al., 2012, Drusenheimer et al., 2015, Zamarbide et al., 2018).…”
Section: Introductionmentioning
confidence: 76%
“…Furthermore, the loss of Lgd function drives the over-proliferation of the imaginal discs, a phenotype that can be rescued by the expression of human CC2D1A or CC2D1B, indicating a functional overlap between these proteins (Drusenheimer et al., 2015). This redundancy was also observed in mammal models, as double CC2D1A/CC2D1B knockout mice died early during embryonic development (Zamarbide et al., 2018), but the deletion of CC2D1A or CC2D1B genes alone does not induce developmental defects (Drusenheimer et al., 2015, Zamarbide et al., 2018). However, non-redundant roles of these proteins are indicated by the perinatal death of CC2D1A-deficient mice (Al-Tawashi et al., 2012, Drusenheimer et al., 2015, Zamarbide et al., 2018).…”
Section: Introductionmentioning
confidence: 76%
“…Two recent studies have further shown that forebrain-specific Cc2d1a cKO mice display reduced memory retention in the novel object recognition and delayed learning in remembering the location of the platform once it was learned in the Morris water maze (Oaks et al, 2017;Zamarbide et al, 2018). In addition to cognitive deficits, we provide further evidence that cKO mice display altered anxiety-like behavior, as evidenced by measuring performance in the OF, EPM, and LDB tests, confirming that CC2D1A is critically involved in regulating anxious behavioral characteristics (Oaks et al, 2017;Zamarbide et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) represents a neurodevelopmental disorder that is characterized by impaired social interaction, repetitive conduct and anxiety-like behaviors (1). Several brain structures and function have been suggested to underlie behavioral abnormalities of ASD including the basolateral amygdala (BLA) (2).…”
Section: Introductionmentioning
confidence: 99%